A study on the effect of advertising on current purchasing: Brand switching and repeat purchasing / Aribah Badzis - Badzis, Aribah (2004)
In markets in which first time purchases are rare, advertising if it work at all, will affects brand switching or retaining customers who otherwise might switch. Actually, in the market place there are three possibilities consequence advertising exposure will be happened on the household's brand choice. It is whether it can increase the probability that the household will change brand (brand switching), or it can induce the household to stay with the brand last purchased (repeat purchasing), or it can effect on choice probabilities. Consequences from the situation, had lead me to do the research that related with the situation. Due to that, the effectiveness of advertising in KFC would be a measure study in this research project. Since the previous advertisement has achieved its objectives, apparently this would be the best time to measure the effectiveness of current advertisement of KFC towards the current purchasing. The study is also specifically to the findings of purchasing relationship between the effect of advertising on the current purchasing whether it is related with the brand switching or repeat purchasing. Therefore, this research also was carried out in order to identify how effective KFC advertising as one of the famous Quick Service Restaurant in Malaysia. This research was carried out through several methodologies such informal interviewing particular staff in KFC Marketing who can contribute useful data and information for my research.